2004
DOI: 10.1038/sj.bmt.1704484
|View full text |Cite
|
Sign up to set email alerts
|

Second autologous transplant with cyclosporin/interferon α-induced graft versus host disease for patients who have failed first-line consolidation

Abstract: Summary:The prognosis for patients with non-Hodgkin's lymphoma (NHL) and advanced Hodgkin's disease (HD) who relapse following autologous transplant is poor. We report on a pilot study designed to evaluate the feasibility of using Cyclosporin A and interferon a to induce autologous GVHD following a second autologous transplant for relapsed lymphoma. In all, 10 patients entered the study with median age 46.5 years. Diagnosis was NHL (n ¼ 7) or Hodgkin's lymphoma (n ¼ 3). All had relapsed from a prior autologous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Nevertheless, their findings are encouraging with reported 5 year PFS and OS of 49% and 54%, respectively. The ability to demonstrate chemosensitivity appears to be an important prognostic feature in several other smaller case series (14, 17, 18). It should be noted that TRM appears to be much higher for HL patients than might be expected for other lymphoma populations.…”
Section: Discussionmentioning
confidence: 92%
“…Nevertheless, their findings are encouraging with reported 5 year PFS and OS of 49% and 54%, respectively. The ability to demonstrate chemosensitivity appears to be an important prognostic feature in several other smaller case series (14, 17, 18). It should be noted that TRM appears to be much higher for HL patients than might be expected for other lymphoma populations.…”
Section: Discussionmentioning
confidence: 92%
“…[17][18][19] The ability of the cytokine to modulate GVHD and GVL after allogeneic BM transplantation has been described primarily in anecdotal case series and although difficult to interpret, clear cases of disease control are evident. [20][21][22] In this study, we have demonstrated that type I-IFN signaling plays an important role in both GVHD and GVL responses. Importantly, the effects of the cytokine are pleiotropic, with differential effects on immune outcomes mediated by donor CD4 ϩ and CD8 ϩ T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Streetly et al 36 approached the problem of relapse after second auto-HSCT using the immunomodulatory agents, CYA and IFN-g, to induce a graft-vs-tumor (GVT) effect in 10 patients (7 NHL and 3 HL). Histological changes consistent with cutaneous GVHD were observed in three patients.…”
Section: Therapeutic Options For Patients With Lymphoma Who Relapse Amentioning
confidence: 99%